Access to a stereoisomer library of solomonamide macrocycles - Jachak, Gorakhnath R.; Athawale, Paresh R.; Choudhury, Rahul; Kashinath, K.; Reddy, D. Srinivasa (Chemistry-An Asian Journal, 2019)
In an attempt towards understanding stereo-structure activity relationships (SSARs), we have prepared eight possible stereoisomers of solomonamide macrocycles, in particular, by changing the stereochemical pattern of non-peptide fragment AHMOA. Here, we have demonstrated different ways to construct three contiguous chiral centers present in solomonamide B macrocycle using substrate/reagent-controlled methods. These methods involve Brown crotylation, NHK reaction and Evans aldol addition as key steps to synthesize key non-peptide fragment. Further, these non-peptide fragments were converted to their corresponding macrocycles via ligand-free intramolecular Heck reaction.
Keywords: Crotylation; Heck reaction; Inflammation; Macrocycles; Stereochemistry